Salam Contract in Online Transactions: A Review Based on the Compilation of Sharia Economic Law - Samsul Muin; M.Arif Mustofa; Reza Okva Marwendi; Al Munip; Kuswanto (Zabags International Journal of Islamic Studies, 2025)
The advancement of digital technology has significantly transformed commercial practices, including the emergence of online transactions that require legal and ethical adaptation in accordance with Sharia principles. In this context, the akad salam, a deferred sale contract in Islamic law, becomes increasingly relevant, particularly within the framework of the Compilation of Sharia Economic Law (Kompilasi Hukum Ekonomi Syariah, KHES). This study aims to examine the validity and relevance of akad salam in online sales based on KHES provisions and to evaluate the compatibility of e-commerce practices with the principles of fiqh muamalah. Employing a systematic literature review (SLR) approach, this research identifies, evaluates, and synthesizes scholarly literature published within the last five years that discusses akad salam, digital transactions, and Sharia economic regulations. The findings indicate that akad salam can be legally applied in online transactions, provided that essential conditions such as clarity of goods, delivery schedule, and upfront payment are fulfilled. However, gaps in understanding among business actors and limitations in digital regulations accommodating Sharia principles remain evident. This article contributes to the field by constructing a conceptual framework that integrates KHES with electronic transaction regulations and offers recommendations for policy enhancement, business education, and future research directions in the development of Sharia-compliant digital commerce.